Analisis Pola Perilaku Pengguna pada Bangunan Kos di Kota Rembang - Queentana Jeoty Valentcia Setiawan Wicaksono; Riandy Tarigan; Robert Riyanto W (Jurnal Talenta Sipil, 2026)
The behavior patterns of boarding house users play a crucial role in designing functional and comfortable temporary living spaces. The growing demand for boarding houses highlights the need to understand user behavior to optimize room design for comfort and productivity. This study aims to analyze user behavior patterns in boarding houses through the lens of behavioral architecture. A descriptive qualitative method was employed, involving direct observation, literature review, precedent studies, and interviews with tenants. Data analysis was conducted using triangulation of sources and content. The case study was conducted at Kos Cemara in Rembang, featuring rooms with dimensions of 3×4 meters and shared kitchen and parking facilities. The results indicate that most user activities are concentrated in the bedroom, serving as the primary personal space. Territorial behavior was observed in circulation and parking areas, where users tended to extend their private zones. Crowding patterns emerged when the number of users or visitors exceeded the parking capacity. The study concludes that room design must emphasize personal comfort and efficient management of communal spaces. This research provides valuable insights for designing adaptive boarding houses, especially in densely populated urban areas.